Caractériser les marges de manœuvre offertes aux aides-soignantes en vue de prévenir les troubles musculosquelettiques dans les établissements pour personnes âgées dépendantes - Sandra Poncet; Sandrine Caroly; Julie Bodin; Yves Roquelaure (Perspectives Interdisciplinaires sur le Travail et la Santé)
Care assistants in nursing homes for the elderly are particularly affected by (MSDs). This article suggests comparing two approaches, one quantitative, the other, qualitative, to characterise the operational leeway offered to care assistants in a nursing home related to MSD prevention. The quantitative approach, based on data from a questionnaire aimed at characterising the perceived offered leeway, partly predicts the actual offered leeway. The qualitative approach, based on ergonomic analysis of activity, shows links between offered leeway and the possibilities for regulation to deal with difficulties encountered with residents. It can contribute to enhancing the questionnaire to make it more representative of the offered leeway. Characterising offered leeway through mixed methods appears to be an interesting tool for revealing factors to build upon and act towards the prevention of MSDs.